Environmental monitoring of airborne fluoro-edenite fibrous amphibole in Biancavilla (Sicily, Italy): a nine-years survey. - Pinizzotto, Maria Rita; Cantaro, Carmelo; Caruso, Maria; Chiarenza, Luciano; Petralia, Carmelo; Turrisi, Sebastiano; Brancato, Antonio (Journal of Mediterranean Earth Sciences, 2018)
Biancavilla was recognized as a National Priority Contaminated Site in 2002 due to environmental dispersion of amphibole fibres with fluoro-edenitic composition. The mining extraction in Monte Calvario quarries and the wide use of sand and rubble in local building industry were responsible for the inhalation of fluoro-edenite fibres by the resident population. Since 2001, environmental and health authorities have promoted a series of remediation and dust mitigation activities in order to reduce the airborne fibre concentration and population exposure. Regional Environmental Agency of Sicily Territorial - Structure of Catania (Agenzia Regionale per la Protezione Ambientale della Sicilia, ARPA Sicilia) has started in 2009 an ongoing airborne fibre monitoring. The present report describes results of fluoro-edenite time trend concentrations obtained from 865 air samples collected in Biancavilla from July, 2009 to November, 2017 and analyzed by scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). Results demonstrate a real improvement of Biancavilla environmental situation and a gradual reduction of exposure as a consequence of the dust mitigation measures. Nevertheless, a continuous environmental follow up should be carefully carried out particularly during high risk fibre releasing activities, such as excavations and demolitions, in order to prevent adverse health effects.